STRUGGLE TO SURVIVE IN RON HOWARD'S CINDERELLA MAN: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HIDAYATULLAH , SYARIF (2006)
This research investigates how struggle to survive influences the major character's psychological development in Ron Howard's Cinderella Man, especially viewed by individual psychological approach. Therefore, the study analyzes the movie in terms of its structural elements and based on the individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two data sources; they are primary and secondary data sources. The primary data source and the object of the study is the movie Cinderella Man itself, meanwhile the secondary ones are any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. A result of the analysis shows the following conclusion: first, Ron Howard wants to utter his idea that struggle to survive should be achieved by working hard and trying to be better than before, and second, struggle to survive which achieved by working hard and trying to be better than before will influence the psychological development of the major character. In this movie, Jim Braddock as the major character has to struggle to survive reinforces his psychological development.